Modelling estuarine wetlands under climate change and infrastructure pressure - Trivisonno, Franco N. (2013)
Abstract: Estuarine wetlands are an extremely valuable resource in terms of biotic diversity, flood attenuation, storm surge protection, groundwater recharge, filtering of surface flows and carbon sequestration. The survival of these systems depends on a balance between the slope of the land, and the rates of accretion and sea-level rise. Climate change predictions for most of Australia include both an accelerated sea level rise and an increase on the frequency of extraordinary river floods, which will endanger estuarine wetlands. Furthermore, coastal infrastructure poses an additional constraint on the adaptive capacity of these ecosystems. In recent years a number of numerical models have been developed in order to assess wetland dynamics and to help manage some of these situations. In this paper we present a wetland evolution model that is based on computed values of hydroperiod and tidal range that drive vegetation preference. Results from a 2D spatially distributed model of wetland dynamics in area E of Kooragang Island (Hunter estuary, NSW) are presented as an example of a system heavily constricted by infrastructure undergoing the effects of sea level rise. Area E presents a vegetation zonation sequence mudflats - mangrove - saltmarsh from the seaward margin and up to the topographic gradient and is compartmentalized by the presence of internal culverts. The model includes a detailed hydrodynamic module (CTSS8), which is able to handle man-made flow controls and spatially varying roughness. The model continually simulates tidal inputs into the wetland and computes annual values of hydroperiod and tidal range to update vegetation distribution based on preference to hydrodynamic conditions of the different vegetation types. It also computes soil accretion and carbon sequestration rates and updates roughness coefficient values according to evolving vegetation types. In order to further explore the magnitude of flow attenuation due to roughness and its effects on the computation of tidal range and hydroperiod, numerical experiments were carried out simulating floodplain flow on the side of a tidal creek using different roughness values. Even though the values of roughness that produce appreciable changes in hydroperiod and tidal range are relatively high, they are within the range expected for some of the wetland vegetation. Both applications of the model show that flow attenuation plays a major role in wetland hydrodynamics and that its effects must be considered when predicting wetland evolution under climate change scenarios, particularly in situations where existing infrastructure affects the flow.